Media Virtual Vs Media Konkret: Peningkatan Kompetensi Dalam Merepresentasi - Erga Kurniawati; Thayban Thayban; La Alio; Kostiawan Sukamto (FKIP Universitas Palangka Raya, 2023)
Representational Competence (RC) can be enhanced with virtual and concrete media. However, the effectiveness of using virtual media is significantly different from concrete media. Recent studies do not fully confirm the use of virtual and concrete media because the materials used have a lower visuospatial level. This study uses a molecular symmetry material with a high visuospatial level. This study aims to compare the effectiveness of using concrete and virtual media on students' understanding of symmetry material. The research was conducted using a quasi-experimental design with 62 students as a sample. The comprehension test instrument has a reliability coefficient based on the Cronbach Alpha test of 0.897. Data analysis was performed with a two-way analysis of variance test. The results show that virtual media is more effective than concrete media in increasing RC and understanding molecular symmetry.